The Duration of Playing Gadgets in Preschool Children Is Related to The Level of Anxiety of Parents - Mareta Ayu Puspa Sari; Nur Eni Lestari; Hari Ghanesia Istiani (Jurnal Keperawatan Terpadu (Integrated Nursing Journal), 2022)
The use of gadgets in preschool children is increasing. This can affect the level of anxiety of parents. This study aim was to determine the duration of playing gadgets for preschool children with the level of parental anxiety. This study used a cross-sectional approach. The independent variable of this study was the duration of playing gadgets, while the dependent variable was the level of parental anxiety. The population of this study was parents who have preschool-age children, with 55 respondents. The sampling technique used total sampling. The research instrument for the duration of the gadget used a checklist. In contrast, the parental anxiety level instrument used a modified GAD-7 (General Anxiety Disorder-7) tested for validity and reliability. Analysis of the research data using Spearman Rho test. The results obtained were p = 0.000 < (0.05), which means that there was a relationship between the duration of playing gadgets for preschool children with the level of parental anxiety with a significant relationship of 0.547 or quite large or strong enough. Things that can be suggested for parents are more supervision of children in using gadgets properly and determining the specified duration.